Optimization of limit value determination in the context of disposal of state property through auction at the Indonesian Audit Board (BPK RI) Representative Office in Jambi Province - Syerlin Juwita; Arif Nugrahanto (Educoretax, 2026)
State Property (BMN) plays a vital role in supporting government functions. Still, over time, many assets experience a decrease in economic and functional value, so they require elimination through an auction mechanism. The elimination of BMN through auction at BPK RI Representative of Jambi Province has been carried out per the regulations, as stipulated in PMK Number 50/PMK.06/2014. This study aims to evaluate the process of determining the limit value in BMN write-off, especially at the BPK RI Representative of Jambi Province, focusing on the effectiveness of procedures and identifying obstacles. Data was obtained through observation and interviews with BMN managers. The results showed that 138 assets with an acquisition value of Rp 197,444,050 experienced an average physical depreciation of 81% and an average functional and economic depreciation of 95.1%, resulting in a limit value of Rp 8,154,608. Although the write-off implementation complies with regulations, obstacles remain regarding officer competence, document completeness, and internal regulation flexibility. This research provides practical contributions in the form of recommendations for optimizing the limit value determination process to support more efficient, transparent, and accountable governance of state assets.